Sistem Resi Gudang Kopi Arabika Gayo dalam Perspektif Kelembagaan Pengelola dan Pengguna di Kabupaten Aceh Tengah - Fadhiela ND, Keumala; Apriyani, Dwi (Department of Agribusiness, Halu Oleo University, 2020)
The problem of agricultural marketing in Indonesia that often occurs is the limited access to capital and falling prices during the main harvest. Therefore, the Warehouse Receipt System (WRS) is a solution for farmers because it can delay sales, protect value, and guarantee commodity prices. Coffee WRS in Central Aceh District has generated funding through 2.5 billion warehouse receipts. However, the interest of coffee farmers to get involved in WRS activities is still very low. The writing of this paper aims to analyze qualitative descriptive information, implementation, and evaluation materials for the government in the implementation of the Gayo Arabica coffee WRS program in Central Aceh District. The study uses qualitative and tiered methods of WRS information using primary and secondary data. The results showed that most farmers found it difficult to meet SRG quality and quality standards so that it also influenced the interest of farmers in the WRS involvement which was still low. Quality assurance and quality become the main attraction for farmers to participate, so WRS activities need to be supported in improving facilities and infrastructure. Public understanding of WRS is still limited so massive socialization is needed. The active role of local government in developing the WRS business also needs to be increased to produce higher WRS productivity.